Numerical simulation of influence of eccentric needle movement on internal flow characteristics of groove-type voc nozzle - Lu, Hongkun; Muhamad, Mat Noor; Kadirgama, Kumaran (Institution of Engineering and Technology, 2022)
The VOC nozzle of the diesel engine is affected by the dynamic characteristics of the needle, and the flow and injection characteristics of each hole are significantly different. In order to improve the spray characteristics of the VOC fuel nozzle, a nozzle structure design is proposed, the main feature is that there is an annular pressure groove on the sealing cone of the needle. In order to study the internal flow characteristics of this structure, a two-fluid model considering the eccentric motion of the needle was established. The results show that the eccentric movement of the needle leads to significant differences in the flow and injection characteristics of each hole. The development of the cavity in hole #1㸦on the side of the needle deviation is earlier than that of hole #2㸦on the deviation side, and the mass flow rate is also larger. After the needle is raised to 100μm, the mass flow rate and flow field characteristics of the nozzle with an annular groove are better than those of the nozzle without the needle groove. The groove structure of the needle acts as a pressure chamber, which is beneficial to weaken the adverse effect of the eccentric movement of the needle on hole #2.